An Assessment of availability, adequacy and utilisation of information and communication technology in universities in South- West, Nigeria (2018)
The study examined the assessment of availability, adequacy, and utilisation of information and communication technology (ICT) in universities in South-West, Nigeria. The ex-post facto design was adopted, to collect information in which three states and three federal universities were purposively selected from South- Western, Nigeria. One hundred students and ten lecturers were randomly selected from each of the three federal universities in the zone. Two validated instruments: Information and Communication Technology Facilities Checklist (ICTFC) and Lecturers’ Questionnaire (LQ, r = 0.82) were used for data collection. Data collected were analysed using descriptive statistics. Between 84% and 100% of the respondents indicated that ICT facilities were available, while between 85% and 100% of them indicated that they were inadequate. The level of utilisation of the ICT facilities is low as indicated by 57%o to 100% of the respondents. Irregular power supply 100%, poor funding 90% and lack of internet facilities 83.33%, were identified as some of the major constraints militating against the use of ICT facilities. It was, therefore, recommended that there should be adequate provision of ICT facilities and resources in our tertiary institutions. The National Universities Commission (NUC) should of a necessity review the course contents of university education, to compulsorily incorporate ICT utilisation as a standard for teaching and learning, while university authorities should support lecturers to utilise ICT facilities while teaching.